Pursuing Pastoral Excellence: Pathways to Fruitful Leadership - Hopkins, Paul E. (Rowman & Littlefield Publishers, 2011)
In Pursuing Pastoral Excellence, pastoral counselor and educator Paul Hopkins aims to help pastoral leaders make a lasting and positive difference in the lives of the people and communities they serve. The heart of this book is the stories of seven ordinary pastors whose leadership has become extraordinary. Their stories not only highlight important characteristics and practices that nurture fruitful pastoral leadership, but they invite readers to examine their own stories, to think about the value of longevity in ministry, and to enhance the enduring impact of their own pastoral leadership. Hopkins frames these stories with a discussion of the difficult vocational challenges pastors are facing in a rapidly changing church milieu and a survey of recent leadership studies. He concludes by exploring seven patterns of pastoral leadership that characterize leaders who have an enduring impact, as well as four key elements coming to be recognized as imperative for the cultivation of enduring pastoral fruitfulness.